STRATEGI THINK, TALK, WRITE UNTUK MENINGKATKAN KETERAMPILAN MENULIS LA DISPONIBILITÉ DAN LA VOLONTÉ - Sri Moerni (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The purpose of this research is to improve writing skills in French on the basic competencies of la disponibilité and la volonté by using Think, Talk, Write strategies for students of class XI IPS 1 in SMA Negeri 10 Yogyakarta in the academic year 2019-2020. The research method used was Classroom Action Research. In this study the initial treatment was given to the impact of the treatment. The results showed 1). The increase in learning outcomes from pre cycle to cycle one was 19.03% and from cycle one to cycle two was 14.29%. 2) With this Think, Talk, write learning strategy, it begins with students understanding the material individually through reading activities, discussing in groups, each group consists of 3 people, and the learning activities end with students writing their ideas independently. Students become more focused and enthusiastic in participating in learning. With the Think, Talk, write strategy, the four stages of language learning competency are passed well, starting from understanding, speaking, reading and writing.